Indigenous materials in libraries and the curriculum - Muñoz-Díaz, Javier, author.
1 online resource (94 pages)
Keywords: "Indigenous Materials in Libraries and the Curriculum: Latin American and Latinx Sources argues for a decolonial engagement with Indigenous peoples' creative works to build awareness of divergent epistemologies and foster healing in the learning community. Exploring how faculty and librarians can collaborate to develop inclusive library collections and curricula, the book demonstrates that this also made possible by supporting Indigenous peoples' reclamation of lands and languages. The authors present practices to build and disseminate collections that showcase the work of Indigenous creators from Latin America and compensate for historical erasure and misrepresentation. Consideration is also given to developing a non-hegemonic curriculum in Indigenous languages and cultures for faculty and students from multicultural backgrounds, particularly Latinx students of Indigenous descent. Above all, the book aspires to facilitate the participation of Indigenous peoples in the scholarly conversation to counteract epistemic and material extractivism and transform the scaffolding of higher education in the current global climate crisis. Indigenous Materials in Libraries and the Curriculum is inspired by a transhemispheric vision to elicit conversation between Indigenous peoples from Latin America (Abiayala) and North America (Turtle Island). The book will appeal to academics, librarians, students, and activists interested in Indigenous languages and cultures, decolonization, DEI initiatives, and library collection development policies that prioritize non-hegemonic narratives"--